The Effectiveness of Instagram Social Media as an Effort to Improve the Quality of Tax Services in the COVID-19 Pandemic in KPP Pratama Ponorogo - Ahmad Suminto; Afif Al Farizi; Nur Kasanah; Meichio Lesmana; Rofi Muzaki (University of Darussalam Gontor, 2021)
Abstract Social Media is media created to facilitate social interaction that is interactive or two way. Social media is based on internet technology that changes the pattern of information dissemination from previously one to many audiences. The purpose of this study is to provide knowledge about how the effectiveness of Instagram social media as an effort to improve the quality of public services during the COVID-19 pandemic. The research method used is qualitative by analyzing content or content based on discourse analysis. The data source is taken from Ponorogo KPP Primary by analyzing the contents of existing content on Instagram social media accounts. The results of this study are that every institution or government agency that has social media such as Instagram on the Ponorogo KPP must pay attention to indicators of measuring service quality, so that in the midst of the pandemic COVID-19 can run effectively and efficiently.